Jumping on the bandwagon : job-hopping trend in Singapore. - Teh, Kai Feng. (2011)
This study attempts to understand the job-hopping phenomena in Singapore. While neo-institutional scholars have emphasized the idea of organizations that are subjected to influences from the environment, they have yet to provide an account on the extent individuals are affected by institutions. The results of this study suggest that the decision to job-hop is largely affected by way our education system is designed rather than personal motivations. Richard Scott's (2001) "three pillars of institutions" was applied to examine the means institutions provide regulatory, normative or cultural-cognitive influences on personal decisions. Through the descriptions provided by interviewees, individual perceptions about their identity as graduate job-hoppers can be analyzed to indicate the extent in which their aspirations are molded by educational institution.